2023
DOI: 10.3389/fimmu.2023.1077531
|View full text |Cite
|
Sign up to set email alerts
|

The potential anti-cancer effects of quercetin on blood, prostate and lung cancers: An update

Abstract: Cancer is caused by abnormal proliferation of cells and aberrant recognition of the immune system. According to recent studies, natural products are most likely to be effective at preventing cancer without causing any noticeable complications. Among the bioactive flavonoids found in fruits and vegetables, quercetin is known for its anti-inflammatory, antioxidant, and anticancer properties. This review aims to highlight the potential therapeutic effects of quercetin on some different types of cancers including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 174 publications
1
5
0
Order By: Relevance
“…through the Akt/mTOR/P70S6K signaling pathway 25 . Emodin, which is another selected compound based on in silico experiments, inhibits cancer growth by suppressing the expression of MMP7, MMP9, VEGF, EMT, N-cadherin, b-catenin, and Snail based on literature data.…”
Section: Studies Have Shown That Another Compound Quercetin Reduces T...mentioning
confidence: 99%
“…through the Akt/mTOR/P70S6K signaling pathway 25 . Emodin, which is another selected compound based on in silico experiments, inhibits cancer growth by suppressing the expression of MMP7, MMP9, VEGF, EMT, N-cadherin, b-catenin, and Snail based on literature data.…”
Section: Studies Have Shown That Another Compound Quercetin Reduces T...mentioning
confidence: 99%
“…Several studies describe quercetin as a unique compound for its high potential to fight cancer-related diseases in many ways. Different concentrations have been evaluated, proving that this bioactive compound suppresses tumor growth of various cancer cell lines, including breast, colorectal, cervical, and lung, among others [ 43 ].…”
Section: Overview Of Polyphenols and Their Anticancer Propertiesmentioning
confidence: 99%
“…Firstly discovered in the early 20th century, quercetin is a widely studied flavonoid with numerous health benefits. Over the years, several studies have demonstrated its protective role in liver diseases (Lotfi et al, 2023; Terao, 2023).…”
Section: Mechanisms Of Polyphenolic Compounds Protect Against Hepatic...mentioning
confidence: 99%